Pemanfaatan Telenursing terhadap Kualitas Hidup Bayi Post Rawat NICU - Rachmayanti Purawita Wardhani; Sigit Mulyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of telenursing is to provide a general overview. It can potentially be used for its effectiveness on the quality of life of premature babies and babies with complex problems after NICU admission. Researchers used a literature study by conducting a journal review regarding telenursing on the quality of babies post NICU care, utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Journals that discuss topics in three categories: 1) Telenursing, 2) Babies with complex problems, 3) Quality of life for babies, and 4) Telehealth. Search via online databases, including ClinikalKey, Elsevier, ScienceDirect, ProQuest, Cambridge, SAGE Journal, 2018-2022, and full-text articles. The research search found ten articles that had been extracted. The research showed that telenursing benefits the quality of life of post-NICU babies. In conclusion, telenursing technology is practical and feasible to improve baby care at home with remote monitoring. Keywords: Premature Baby Life, Telenursing